Lessons from Human Error: Building Airport Safety Culture - Andi Frianto Peranginangin; Muhammad Nur Cahyo Hidayat Nasrullah; Olin Yahya Malau; Hadi Prayitno (Penerbit Goodwood, 2025)
effectiveness of Apron Movement Control (AMC) supervision in developing a safety culture at the apron of a major airport in North Sumatra. It was motivated by a collision between a Lavatory Service Truck (LST) and a Boeing 737-800 aircraft on October 16, 2024, caused by personnel negligence, unserviceable equipment, and weak supervision. Methodology: A qualitative case study approach was applied. Data were collected through observation, interviews, and documentation, and analyzed thematically using NVivo 15. The ORLIO model was employed to evaluate human error. Result: The study identified repeated violations—normalization of deviance among Ground Support Equipment (GSE) personnel, limited AMC supervision, and non-compliant equipment. ORLIO-based evaluation enhanced personnel reflection and safety awareness, while AMC supervision acted as external enforcement. The synergy between reflection and supervision contributed to a shift in apron safety culture from permissive toward a more mature and sustainable one. Conclusions: The apron accident shows that safety failures stem not only from individual errors but also from the interaction of human, equipment, and supervisory factors. Integrating ORLIO and AMC supervision effectively enhances safety awareness and procedural discipline. Limitations: The study is limited to one airport, with qualitative data that may involve subjectivity. It focuses on operational staff, excluding higher management, and does not assess long-term impacts quantitatively. Contribution: The study was limited to one airport, so findings may not represent all contexts. It contributes to aviation safety management by demonstrating how combining human error evaluation and AMC supervision strengthens apron safety culture, offering practical insights for airport authorities and regulators.